2011
DOI: 10.1007/s13205-011-0031-7
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics and identification of efficient strains of Azospirillum in maize ecosystems of Bihar (India)

Abstract: Information on inoculum load and diversity of native microbial community is an important prerequisite for crop management of microbial origin. Azospirillum has a proven role in benefiting the maize (Zea mays) crop in terms of nutrient (nitrogen) supply as well as plant growth enhancement. Bihar state has highest average national maize productivity although fertilizer consumption is minimum, indicating richness of Azospirillum both in terms of population and diversity in soils. An experiment was planned to gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The observations in this experiment on rhizosphere microbial and rhizoplane fungal population clearly indicated that the counts increased significantly with the crop advancement ascribed to the progressive mineralization of the litter fall from the crops, root exudates and added crop residues and enhanced availability of organic substrates for provision of food and increase in the population of microbes. Our results concur with that of Verma et al [60] and Bashan et al [61] who observed an increased trend in the preponderance of Azot and Azosp strains with an increase in organic carbon level from 0.2-1.0%.…”
Section: Microbial Populationsupporting
confidence: 93%
“…The observations in this experiment on rhizosphere microbial and rhizoplane fungal population clearly indicated that the counts increased significantly with the crop advancement ascribed to the progressive mineralization of the litter fall from the crops, root exudates and added crop residues and enhanced availability of organic substrates for provision of food and increase in the population of microbes. Our results concur with that of Verma et al [60] and Bashan et al [61] who observed an increased trend in the preponderance of Azot and Azosp strains with an increase in organic carbon level from 0.2-1.0%.…”
Section: Microbial Populationsupporting
confidence: 93%
“…The benefits of plants inoculated with Azospirillum was not only associated to its capacity to fix atmospheric N2, but also to its ability to synthesize phytohormones, indole-3-acetic acid (Fukami et al, 2018). In the soil, the distinct impact on preponderance of Azospirillum in maize rhizosphere varied, contributing to distinct physio-chemical factors and history of land use patterns (Verma et al, 2011). The application of biofertilizer proliferated the population of PSB compared to the treatment without biofertilizer.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to form plant hormones has been postulated as a major property of PGPR in general and specifically, by the species of Azospirillum (Tsavkelova et al 2006). Verma et al (2011) showed that 88% of the evaluated Azospirillum strains (50 isolates) from maize soils were poor in IAA production indicating a substantial variability among Azospirillum strains for IAA production. The variation in the ability of plant growth promoting bacteria to produce IAA had also been observed earlier (Zahir et al 2000;Majeed et al 2015).…”
Section: Discussionmentioning
confidence: 99%